16p13.11 microduplication in 45 new patients: refined clinical significance and genotype–phenotype correlations. Issue 5 (4th October 2018) - Allach El Khattabi, Laïla; Heide, Solveig; Caberg, Jean-Hubert; Andrieux, Joris; Doco Fenzy, Martine; Vincent-Delorme, Caroline; Callier, Patrick; Chantot-Bastaraud, Sandra; Afenjar, Alexandra; Boute-Benejean, Odile; Cordier, Marie Pierre; Faivre, Laurence; et al.
Abstract : Background: The clinical significance of 16p13.11 duplications remains controversial while frequently detected in patients with developmental delay (DD), intellectual deficiency (ID) or autism spectrum disorder (ASD). Previously reported patients were not or poorly characterised. The absence of consensual recommendations leads to interpretation discrepancy and makes genetic counselling challenging. This study aims to decipher the genotype–phenotype correlations to improve genetic counselling and patients' medical care. Methods: We retrospectively analysed data from 16 013 patients referred to 12 genetic centers for DD, ID or ASD, and who had a chromosomal microarray analysis. The referring geneticists of patients for whom a 16p13.11 duplication was detected were asked to complete a questionnaire for detailed clinical and genetic data for the patients and their parents. Results: Clinical features are mainly speech delay and learning disabilities followed by ASD. A significant risk of cardiovascular disease was noted. About 90% of the patients inherited the duplication from a parent. At least one out of four parents carrying the duplication displayed a similar phenotype to the propositus. Genotype–phenotype correlations show no impact of the size of the duplicated segment on the severity of the phenotype. However, NDE1 and miR-484 seem to have an essential role in the neurocognitive phenotype. Conclusion: Our study shows that 16p13.11 microduplications are likely pathogenic when detected in the context of DD/ID/ASD and supports an essential role of NDE1 and miR-484 in the neurocognitive phenotype. Moreover, it suggests the need for cardiac evaluation and follow-up and a large study to evaluate the aortic disease risk.